Improvement of Speech Skills Using Experiential Learning Method in Kindergarten (Classroom Action Research at Siloam Kindergarten Surakarta) - Prastawa, Singgih; Sumardiono, Sumardiono; Naufal, Dhiwangkara Arno (Journal of English Language and Education, 2025)
English is an international language and the medium of today's learning, especially in 21st century learning. In fact, in kindergarten (TK), everything is not mastered and even taught because it refers to language skills. There are 2 language skills taught in kindergarten which are listening and speaking. Speaking is highly recommended especially at an early age to become a habit, in fact in kindergarten there are still many who are not familiar with the language. This happens in Siloam Surakarta Kindergarten, although it is often taught but not fully mastered. From that, the purpose of this research is to find out the improvement of speaking skills in English for students at Siloam Kindergarten Surakarta. The method used in this research is classroom action research (PTK). The research subjects were small large class students (Kindergarten A Kindergarten B) totalling 20 respondents. The data collection instrument in this research is using tests, interviews and observations. The cycle was carried out in 2 cycles. The stages in this PTK are planning, action, observation, reflection. The results were analysed with excel related to the test results before PTK and after PTK. The results in cycle I of this study showed that the learning was carried out using the Experiential method, showing the average in English speaking learning outcomes was 50. But after cycle II, learning using Experiential learning methods adapted to the stages of PTK, then get a score 60 for the average. Based on these results, the experiential learning method is suitable to be applied in kindergarten especially in learning to speak in English.